50 years after deinstitutionalization mental illness in contemporary communities. - Perry, Brea L. (Advances in medical sociology ;, 2016)
Throughout the 1960s and 1970s, a revolution in mental health policy and practice known as deinstitutionalization occurred in Europe and the US. This movement was catalyzed by criticisms of psychiatric institutions and resulted in the release of thousands of people with serious mental illness from long-term care facilities into the community. It is acknowledged that these reforms held great promise, but have had numerous unintended negative consequences. Moreover, deinstitutionalization has strained the resources and reach of community-based mental health treatment systems, spilling into other institutions such as criminal justice and education. Volume 17 of Advances in Medical Sociology will examine deinstitutionalizations legacies approximately 50 years after reintegration began, turning a critical lens toward contemporary problems and solutions related to mental illness in countries where reform occurred. This volume will highlight pressing issues around mental health treatment, social and health policy, and the lived experiences of people and families coping with mental illness that were or continue to be significantly influenced by deinstitutionalization reforms.